2019
DOI: 10.17711/sm.0185-3325.2019.014
|View full text |Cite
|
Sign up to set email alerts
|

The desire to hasten death in advanced cancer patients at a Mexican palliative care service

Abstract: Introduction. The desire to hasten death (DHD) might be present in patients with advanced cancer. Multiple distressing physical and psychosocial symptoms may be related to it. There is limited literature about the characteristics of these patients in México. Objective. To describe the prevalence and factors associated with DHD in advanced cancer patients evaluated by a palliative care psychiatrist. Method. We conducted a cross-sectional study, including all patients referred to psychiatric assessment at the Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
4
0
3
Order By: Relevance
“…To the best of our knowledge, this study is the first to describe the prevalence and associated factors of the DfD of palliative patients cared for in a HPCU. Our results indicate that 20% of patients endorse a significant and persistent desire for hastened death are aligned with earlier studies (Chochinov et al, 1995;Rodríguez-Mayoral et al, 2019), along with the Portuguese research by Julião et al (2013) in terminally ill persons in a PC Unit.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this study is the first to describe the prevalence and associated factors of the DfD of palliative patients cared for in a HPCU. Our results indicate that 20% of patients endorse a significant and persistent desire for hastened death are aligned with earlier studies (Chochinov et al, 1995;Rodríguez-Mayoral et al, 2019), along with the Portuguese research by Julião et al (2013) in terminally ill persons in a PC Unit.…”
Section: Discussionsupporting
confidence: 92%
“…The benefits of improving MDD diagnosis in advanced cancer patients are considerable. Timely diagnosis translates to improved treatment and better mental health which could impact in quality of life, physical symptoms, treatment compliance, suicidal risk, wish to hasten death, and survival rates (Lloyd-Williams et al, 2004; Kroenke et al, 2010; Pinquart and Duberstein, 2010; Rodríguez-Mayoral et al, 2019, 2020). Large-scale studies with considerable follow-up have consistently shown the beneficial effect of depression treatment in patients with good or bad prognosis malignancies, both in terms of reducing major depression and improving quality of life (Mulick et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its high frequency, MDD represents a source of morbidity and negatively impacts survival in patients with advanced cancer. Among its many repercussions, MDD is associated with worse functioning, survival rates, quality of life, and treatment compliance, as well as with wishes to hasten death and a higher frequency and intensity of physical symptoms (Lloyd-Williams et al, 2004; Kroenke et al, 2010; Pinquart and Duberstein, 2010; Rodríguez-Mayoral et al, 2019, 2020). Although it is a common complication, it is underdiagnosed and therefore undertreated (Sharpe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A duração média da sobrevida até a morte variou de 63 dias a 29,96 meses [13][14]17 . Os tipos mais prevalentes de câncer foram de próstata [18][19][20] , pulmão 12,18 , ginecológicos 19 , mama 19 e colo retal 20 . Apenas um estudo foi realizado com pacientes diagnosticados com HIV 16 .…”
Section: Cuidados Paliativosunclassified
“…A pesquisa desenvolvida nos EUA, a partir de registros de 64 suicídios concretizados de pacientes com câncer, identificou que 44,0% dos suicídios aconteceram durante a abordagem paliativa, 38,0% possuíam prognóstico ruim, 47,0% apresentavam dor e 17,0% problemas de sono 18 . Em contrapartida, outro estudo levantado aponta que os cuidados paliativos foram associados à diminuição da probabilidade de suicídio (OR=0,19; 0,08 -0,47) 12 .…”
Section: Cuidados Paliativosunclassified